Phylogenetic measures applied to the conservation of Mexican marsupials - Irene Goyenechea (Revista Mexicana de Biodiversidad)
The didelphimorphs in Mexico are found all over the country except for the Baja California Peninsula. The aim of this study was to use three methods to assess the phylogenetic diversity of the species: Marmosa mexicana, Tlacuatzin canescens, Caluromys derbianus, Chironectes minimus, Didelphis marsupialis, Didelphis virginiana, Metachirus nudicaudatus and Philander opossumdistributed in the Mexican biogeographic provinces, and to determine the potential conservation areas for these mammals.  Phylogenetic information was included to execute the taxonomic weighting, taxonomic dispersion and taxonomic distinctness within the Mexican biogeographic provinces.  In addition a gap analysis was performed to show which protected areas contain the didelphimorphs under a conservation category. Considering phylogenetic diversity with the former analysis, results indicate that the biogeographic provinces most important for conservation of didelphimorphs are the Gulf of Mexico, the Pacific Coast and Oaxaca but also have to be considered Soconusco and Sierra Madre del Sur. We also observed that not all of the richest sites corresponded with current protected areas. This study is important because it employed different conservation approaches based on phylogenetic measures and was focused on Mexican marsupials from which one species is endemic and two are under conservation concern.